1981
DOI: 10.1073/pnas.78.1.210
|View full text |Cite
|
Sign up to set email alerts
|

Biological reactivity of hypochlorous acid: implications for microbicidal mechanisms of leukocyte myeloperoxidase.

Abstract: Oxidative degradation of biological substrates by hypochlorous acid has been examined under reaction conditions similar to those found in active phagosomes. Iron sulfur proteins are bleached extremely rapidly, followed in decreasing order by f3carotene, nucleotides, porphyrins, and heme proteins. Enzymes containing essential cysteine molecules are inactivated with an effectiveness that roughly parallels the nucleophilic reactivities of their sulfhydryl groups. Other compounds, including glucosamines, qumiones,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
241
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(249 citation statements)
references
References 44 publications
5
241
0
1
Order By: Relevance
“…It can oxidize thiols and other biological molecules including, ascorbate, urate, pyridine nucleotides, and tryptophan [50,51]. HOCl chlorinates several compounds such as amines to give chloramines; tyrosyl residues to give ring chlorinated products, cholesterol and unsaturated lipids to give chlorohydrins, and it can also chlorinate DNA [52].…”
Section: Hypochlorous Acid (Hocl)mentioning
confidence: 99%
“…It can oxidize thiols and other biological molecules including, ascorbate, urate, pyridine nucleotides, and tryptophan [50,51]. HOCl chlorinates several compounds such as amines to give chloramines; tyrosyl residues to give ring chlorinated products, cholesterol and unsaturated lipids to give chlorohydrins, and it can also chlorinate DNA [52].…”
Section: Hypochlorous Acid (Hocl)mentioning
confidence: 99%
“…45 No such specificity was observed with HOCl, another SH oxidizing reagent, which even at mM concentrations inhibited all 11 enzymes in the pathway. 46 Recently, it has been reported that the exquisite sensitivity of GADPH to peroxide is conferred by a specific selenocysteine located at the catalytic site of the enzyme. 47 Another example of a low-affinity peroxide effect is its inhibition of skeletal muscle Ca 2 ĂŸ -activated K ĂŸ channel, which in artificial bilayers showed a K i 410 mM.…”
Section: Discussionmentioning
confidence: 99%
“…[151]), although protein damage and DNA-protein cross-linking were directly studied only to a limited extent [152]. Damage to mitochondrial electrontransport proteins by hypochlorite [153] and other agents has been studied, and noted to be enhanced by vitamin E deficiency [154]. Mitochondria exposed to exogenous radicals lose control of ion balance, notably of calcium transport ; protein oxidation as well as proteolysis may be important in such changes [145,155,156].…”
Section: Protein Oxidation In Isolated Organelles and Other Complex Smentioning
confidence: 99%